Confessional Narrative in Leonid Andreev’s “Thought” and “My Notes” - Chieh-han Chiang (Studia Litterarum)
This paper examines the role of confessional discourse in Leonid Andreev’s “Thought” and “My Notes.” In these works, confession not only serves as a significant narrative device that creates a particular mode of psychological reality. It is also directly related to the interpretation of the meaning of the stories. On the one hand, the confessional intention presented in the texts shows the struggle to gain self-knowledge and the urgency of overcoming the isolation of one’s existence. On the other hand, it does not lead to the discovery of truth and only unveils its elusive quality. With a particular focus on the representation of existential consciousness and the realization of the poetics of play, this study examines, among others, the principle of dialogism and the significance of paratextual elements. The paper argues that the desire for selfdisclosure reflected in “Thought” and “My Notes” reveals the paradoxical nature of the confessional narrative, which is transformed into a certain kind of play, leading to selfdeception and the fictitious construction of identity.